DILEMA WASIAT ANTARA KEHENDAK PEWARIS DAN HAK MUTLAK AHLI WARIS: KAJIAN KOMPARATIF BATASAN TESTAMENTAIR DALAM HUKUM PERDATA DAN HUKUM ISLAM - Mujennih; Khodijah Nur Tsalis (The Juris, 2025)
In the Civil Law system, the protection of direct line heirs (legitimaries) is guaranteed through the concept of Legitime Portie (LP) or the Forced Share. A will that violates the LP is not automatically void by law, but rather is voidable and must be actively challenged through the mechanism of reduction (inkorting) by the disadvantaged heir within one year after the succession opens. This principle demonstrates the strong validity of the testator's will if the heir chooses not to file a claim. Meanwhile, in Islamic Law (KHI - Compilation of Islamic Law), the testator's will is quantitatively limited, where a bequest (wasiat) can only be valid for the beneficiary up to a maximum of 1/3 of the estate left by the testator. A will exceeding this limit can become valid if there is an agreement among the heirs who receive the inheritance. However, case studies in the Religious Courts demonstrate jurisprudential flexibility, where the 1/3 KHI limit can be set aside (Supreme Court Decision No. 34K/Pdt.G/2022) if the remaining heirs are classified as distant relatives (Dzawil Arham) whose position is ambiguous in the KHI, thus making the authority of the testator's will more dominant.